Medical student attitudes on vaccination relevance: a mixed-method study - Herrmann-Werner, Anne; Festl-Wietek, Teresa; Gille, Christian; Zipfel, Stephan; Wiechers, Steffen (PLOS ONE, 2022)
The study aims to investigate the attitudes of medical students regarding the importance and relevance of vaccinations, whether vaccinations should be compulsory and how to employ a new teaching concept to deal with vaccination-critical parents.
Gesehen am 02.11.2023